Supplementary Activities Augmenting the General English Program in Higher Education: Student Engagement and Teachers’ Perspectives - Cuong, Pham Huy; Nghia, Vo Trong (VNU Journal of Science: Education Research; Vol 40 No 4DO - 10.25073/2588-1159/vnuer.5016, 2024)
Given the diverse availability of affordances and learning opportunities in multiple settings, language learning is no longer confined to classroom boundaries. With teachers’ scaffolding and support, learners can develop autonomous learning strategies drawing on the resources within and beyond traditional classrooms. This study aims to explore teachers’ perspectives on the value of supplementary learning activities in augmenting the General English Program (GEP) at a university in Vietnam with a particular emphasis on learner engagement in these activities outside classroom settings. The data are based on the statistics of students’ attendance and performance in the supplementary activities currently implemented at the university and interviews with eight GEP teachers. Findings show that the students were partially cognizant of the learning opportunities implicated in supplementary activities and demonstrated relatively active engagement and performance. The teachers also acknowledged that these activities contributed positively to students’ holistic language development as a complement to the GEP. The study has significant implications for educational stakeholders in curriculum design and deployment of supplementary learning activities that facilitate learner engagement in language practice outside classrooms.